Kulturowe aspekty broni średniowiecznej w refleksji Andrzeja Nadolskiego - Iwańczak, Wojciech (Acta Universitatis Lodziensis. Folia Archaeologica, 2012)
This article aims at highlighting a broader context of research interests on arms and armour conducted by Andrzej Nadolski. From the beginning of his scientific career, he believed that studies in arms were a part of the history of society and its culture. In terms of methodology he always supported the farreaching comparative studies, but he also recommended great caution in drawing general conclusions. To build a complete picture of place of weapons in past societies he called for detailed studies of iconography on par with research on material culture. Temperance in the formulation of decisive conclusions accompanied by kindness towards polemics, he believed that these qualities were necessary for practicing the scientific approach towards humanities in general, towards studies in weaponry as well. He saw this discipline as a rather narrow field of research, nevertheless he always emphasized its great significance. If war was one of the most important events in history, one should never underestimate the role of weapons. He also suggested that arms should always be viewed in a broader context, as a component of literature, culture and art. Andrzej Nadolski had high demands of other researchers, but also extended same criteria towards himself. He was very critical of his own accomplishments, a trait not shared by the majority of scientists. His ambition was not to restrict himself to a narrow field of specialization in one discipline, which was the reason for his participation in popularization of humanities in mass media, with significant results. Andrzej Nadolski never treated weapons out of a broader context, always seeing them as an important part of widely undestood human activities, which comprise the depth of humanistic character of his work.